Evaluating Questioning Skills of Pre-Service EFL Teachers Through Self-Evaluation of Teacher Talk (SETT) in Microteaching Class - Naila Muroda; Ahmad Munir; Slamet Setiawan (Linguistic, English Education and Art (LEEA) Journal, 2020)
This study aims to investigate pre-service EFL teachers’ way evaluating their own teachers talk, especially in questioning skill using SETT (Self-Evaluation of Teacher Talk). The method used in this study is qualitative research toward four pre-service EFL teachers’ used as the research’s participants. By revealing the data, the author used teachers’ reflective journals as process for evaluation and also interview to obtain deeper perspective and feelings results of the data analysis. The findings indicated that doing the evaluation of questioning skills using SETT framework has helped their awareness of their language used in teaching, not only about the interactional features for communication but also how manage the language to assist the students to response. More importantly, they are able to use and control their language in running the classroom activities. Thus, it means that SETT has helped the teachers to achieved their personal development and awareness toward the classroom communication in holding the interaction especially in questioning skills. Keywords: Questioning Skills, SETT, Pre-service EFL Teachers